CLEANING OF THE AIRWAYS WITH THE METHOD OF A HIGH-FREQUENCY CHEST WALL OSCILLATION IN THE TREATMENT OF CHILDREN SUFFERING FROM THE CYSTIC FIBROSIS - O. I. Simonova; О. А. Ereshko; D. А. Makarova; S. Yu. Semykin; I. Yu. Asaturova; V. Yu. Brisin; K. S. Volkov; А. Yu. Tomilova (Вопросы современной педиатрии)
Background: The basis of the treatment of patients with cystic fibrosis (CF) is kinesitherapy — a special respiratory gymnastics and drainage of a bronchial tree. The increase of efficiency of a complex of medical rehabilitation measures can be reached by the application of a method of the high-frequency chest wall oscillation (HFCWO). Aim: To develop additional criteria of the individual program of classes by HFCWO system for children with CF. Patients and methods: The research involved 43 children with CF at the age of 2 years 10 months — 17.5 years whose treatment included 14 HFCWO procedures. During the first 4 classes 10 children from them received the oscillations calculated according to the age, and from the 5th class — according to the severity of CF course and indicators of a volume of the forced expiration for the first second (VFE1) — subgroup I. The patients, included in the subgroup II (n = 33), from the first occupation received the oscillations calculated on the severity of CF course and according to VFE1 indicators. Results: In the subgroup I during the first 4 classes there were no improvements of the peakflowmetry indicators (р >0.05), all children had complaints to discomfort from the procedure. From the 5th class clinical functional dynamics started being noted, to the 8th class indicators amounted to the subgroup II in which positive changes were registered from the first class. To the 14th occupation the VFE1 indicators improved in I and II subgroups: with a high CF severity (from 42.5 ± 5.5 to 58.1 ± 1.6%; р = 0.015) and with a course of medium severity (from 71.1 ± 1.2 to 80.0 ± 2.8%; р = 0.025). In addition all patients showed the improvement of the peakflowmetry indicators and excursion of a chest wall (cm; р <0.05), including patients with a high CF severity (р = 0.012). Conclusion: The efficiency of the classes with application of the HFCWO method, focused on the CF severity and VFE1 indicators, is higher than application of a method taking into account the age of patients.